Survei Motivasi Beraktivitas Fisik Masyarakat Dusun Kalenanyar - Aziz Nurfalah Tsani; Gani kardani; Muhammad Nurzaman; Ucu Abdul Ropi (Universitas Galuh, 2024)
ABSTRACTThis study aims to understand the motivation of physical activity in the Kalenanyar Hamlet community. The research method used in this study is descriptive analysis. The Kalenanyar Hamlet community has 15 members. The research instrument used to understand the Physical Activity Motivation Survey is the Motivation Questionnaire. The results of the research and analysis were carried out by researchers to understand amotivation, external regulation, introjected regulation, and intrinsic regulation. My answer in the statement